Connecting the dots through interdisciplinary literary studies: psychoanalysis, cosmopolitans, mental health, poverty, and urbanism. book review: Ankhi Mukherjees unseen city: the psychic lives of the urban poor, 2021, Oxford University Press. 263 pages - Seng, Tong Chong; Abd Rahman, Ahmad Zufrie; Abu Bakar, Roslina (Sci and Tech Universal Inc, 2024)
This paper reviews the conceptual and theoretical framework propounded by Ankhi Mukherjee. Her framework is developed through rigorous analyses of literary texts from diverse genres. It is philosophically underpinned in psychoanalysis and postcolonial studies. The interdisciplinary framework is eclectic in nature and it can be used in trauma studies, ageing population, mental health, health communication, and urban studies. This paper delineates the development of the framework and its application